Cancel Culture as a Sanction for Members of the Academic Community Involved in Sexual Violence - Vitrana, Mokhamad Gisa; Islamiah, Kiki Rizki; Oktavianus, Afriman (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
Imposing sanctions on academics involved in sexual violence on campus is often challenging, mostly because of the significant influence these individuals wield over academic advancement and institutional growth. This influence often leads to disappointment among victims and the campus community, as the sanctions imposed tend to be lenient. Relevant aspects of sexual violence committed by members of the academic community, particularly academic perpetrators, such as his scientific works, programs, and other academic initiatives, often continue to receive special recognition on campus. This is despite their close connection to the acts of sexual violence committed. On the other hand, cancel culture has emerged as a new form of sanction, primarily created through social media, reflecting public disappointment toward individuals who violate societal norms. Cancel culture, as a form of public sanction, has a significant impact on norm violators, resulting in their rejection by the public and the dismissal of their associated works. However, the Indonesian Minister of Education, Culture, Research, and Technology Regulation No. 30 of 2021 on the Prevention and Handling of Sexual Violence in Higher Education Institutions does not specifically include cancel culture as a sanction. The purpose of the research focuses on the extent to which cancel culture can be applied as a sanction for members of the academic community involved in sexual violence. This research uses a normative method with qualitative descriptive data analysis.